Customer-related performance and the relevance of environmental reporting. (20th July 2018) - Radhouane, Ikram; Nekhili, Mehdi; Nagati, Haithem; Paché, Gilles
Abstract: Based on the fact that shareholders respond to environmental initiatives according to their perception of the potential related benefits, this study investigates whether customer-related performance affects the value relevance of voluntary environmental reporting. This paper provides a better understanding of the circumstances under which shareholders react positively to voluntary environmental information disclosed by firms operating in environmentally sensitive industries. Using a sample of French listed firms belonging to the SBF 120 stock index over an eleven-year period (2001–2011), our results show that a higher level of environmental disclosure is valued negatively by shareholders for firms operating in environmentally sensitive industries. In line with cost-benefit analysis, shareholders are found to rely more on profitability-based performance (i.e., return on sales and return on assets) than on revenue-based performance (i.e., sales growth) when assessing the relevance of environmental reporting for firms operating in environmentally sensitive industries.